Ti3C2Tx-Nb2Mo3O14 composite as novel anode to realize high power density combined with high stability in a hybrid lithium-ion capacitor - Pawar, Meenakshi D.; Thripuranthaka, Marulasiddappa; Patrike, Apurva; Deshmukh, Ashvini B.; Chaturvedi, Vikash; Krishnan, Arun; Shivade, Rajkiran; Shelke, Manjusha V. (Energy Technology, 2023)
Lithium-ion capacitors (LICs), with their higher energy density at high power capability, stand out as the future generation of energy-storage devices. Herein, the nanocomposite of Ti3C2Tx MXene with Nb2Mo3O14 is prepared by a one-step hydrothermal method and studied as an electrode material for LIC. The asfabricated composite MXene niobium molybdenum oxide (MXNMO) achieves a high reversible capacity of 205 mAh g(-1) at 100 mA g(-1) current density with outstanding cyclability. Further, asymmetric LIC full-cell device composed of MXNMO anode with supercapacitor grade activated carbon as a cathode delivers an energy density of 37.8 Wh kg(-1) (0.25 A g(-1)) and a higher power density of 4244 W kg(-1) (5 A g(-1)) along with the excellent durability showing 85% capacitance retention over 4000 cycles at 0.5 A g(-1).
Keywords: lithium-ion capacitors; MXene; niobium molybdenum oxides; pseudocapacitive anode materials